Vocalismo acentuado do Noroeste português - descrição acústica, variação dialectal e representação fonológica - Brissos, Fernando (2018)
The paper's aim is two-fold: 1, to give an acoustical depiction of the vowel systems of Portuguese northwestern dialects; 2, to establish a correlation between those vowel systems and the ones that can be found in central-southern Portuguese varieties. The data call for a revision of some important aspects of Portuguese dialectology, namely: a) the description of northwestern dialects, as different types of diphthongs are found in different areas than the ones pointed out by dialectal studies; and b) the adequacy of the phonological vowel system traditionally used to describe European Portuguese as a means of representation of the continental dialectal varieties. Seven different systems are needed to represent all dialects comprised in this study.